2019
DOI: 10.4018/978-1-5225-7479-8.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Riding the Wave

Abstract: To date, most of the literature on female entrepreneurship reveals a paucity of research on developing market contexts. The authors build on this to establish the constraining challenges and barriers faced by Pakistani women entrepreneurs. In this chapter, they adopt the perspective of institutional logics as a particular reference point due to its influence in shaping entrepreneurial action. The choice of adopting a contextual approach also aims to highlight differences to Western models where institutional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Female entrepreneurial intention can not only be enhanced in a significant and positive way with the help of relevant entrepreneurial knowledge but it can also enhance the rate of success of female entrepreneurs who take a decision to pursue their dreams that step towards being self-made with unique and out of the box ideas (Hussain & Mahmood, 2012). In line with these studies and theirs the seven of the hypotheses were accepted whereas one was rejected according to the theory (Muhammad, Warren, & Binte-Saleem, 2017), financial support and resources make the females self-efficient and increase their level of self-efficacy as well, all of which in turn enhances the possibility of increase in female entrepreneurial intention (Omeihe, Dakhan, Khan, Gustafsson, & Amoako, 2019). Once the orientation towards goal is clear, the efforts become more vivid and are enhanced and then so it the goal for achieving an entrepreneurial dream becomes more important so female entrepreneurial intention clearly enhances (Ahmad, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…Female entrepreneurial intention can not only be enhanced in a significant and positive way with the help of relevant entrepreneurial knowledge but it can also enhance the rate of success of female entrepreneurs who take a decision to pursue their dreams that step towards being self-made with unique and out of the box ideas (Hussain & Mahmood, 2012). In line with these studies and theirs the seven of the hypotheses were accepted whereas one was rejected according to the theory (Muhammad, Warren, & Binte-Saleem, 2017), financial support and resources make the females self-efficient and increase their level of self-efficacy as well, all of which in turn enhances the possibility of increase in female entrepreneurial intention (Omeihe, Dakhan, Khan, Gustafsson, & Amoako, 2019). Once the orientation towards goal is clear, the efforts become more vivid and are enhanced and then so it the goal for achieving an entrepreneurial dream becomes more important so female entrepreneurial intention clearly enhances (Ahmad, 2011).…”
Section: Discussionmentioning
confidence: 77%
“…In compensating for the weaknesses of the law courts, the findings revealed that indigenous institutions, such as ties to cultural, religious and trade associations had evolved to fill the role of formal institutions. Specifically, the article also revealed how the respondents relied on networks of family relationships to develop trust; thereby enhancing their access to market information (Child et al, 2002;Oviatt & McDougall, 2005;Amoako & Lyon, 2014;Amoako, 2019). Specifically, the received knowledge is particularly important in the African context, as it is customary for members to support the enterprise of a family/kin.…”
Section: Discussionmentioning
confidence: 99%
“…Put succinctly, the core assumption behind the institutional rivalry presupposes an understanding of entrepreneurial behaviour located within institutional contexts. This is particularly important as identities, values, norms and beliefs have been acknowledged to shape entrepreneurial relations (Jenssen & Kristiansen, 2004;Chao & Moon, 2005;Omeihe, Dakhan, Khan, Gustafsson, & Amoako, 2019). Where formal institutional arrangements are perceived to be congruent to the interest of social groups, actors within such groups will be motivated to rely on alternative arrangements that promote their economic and social interest.…”
Section: A Contextual Perspective Of Weak Institutional Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of these conventions, women should be instructed to wear the hijab rather than engage in business. Although the lack of access to financing has been a source of worry, Pakistani women entrepreneurs face particularly difficult obstacles (Omeihe et al, 2019). Therefore, the current study explored the role of religion and culture on female entrepreneurs in Pakistan.…”
Section: Methodsmentioning
confidence: 99%